Biweekly gemcitabine and cisplatin in platinum-resistant/refractory, paclitaxel-pretreated, ovarian and peritoneal carcinoma - Bozas, G.; Bamias, A.; Koutsoukou, V.; Efstathiou, E.; Gika, D.; Papadimitriou, C.A.; Dimopoulos, M.A. (Gynecologic Oncology, 2007)
Objectives: Synergism between gemcitabine and cisplatin is supported by preclinical and clinical data. The present study explores the efficacy of a biweekly regimen in platinum-resistant/refractory, paclitaxel-pretreated ovarian and peritoneal cancer. Methods: 50 paclitaxel-pretreated patients with platinum-resistant/refractory ovarian or peritoneal carcinoma who had previously received paclitaxel chemotherapy, were treated with six cycles of gemcitabine 1000 mg/m2 followed by cisplatin 40 mg/m2 on days 1 and 15, repeated every 4 weeks. Results: The median platinum-free interval (PFI) was 4 months while the median number of previous treatment lines was 2. Chemotherapy was well tolerated. Objective responses were observed in 31.5% of evaluable patients (n = 35). CA125 response was observed in 68% of patients with elevated CA125 (n = 41). Median overall survival (OS) was 13.2 months (95% Confidence Interval, CI: 10.2-16.2) while progression-free survival (PFS) was 4.9 months (95%CI: 3.5-6.4). A PFI of less than 3 months was associated with lower objective response rates (15.8% versus 50%, p = 0.03). Conclusions: Biweekly gemcitabine and cisplatin is feasible for patients with platinum-resistant ovarian or peritoneal cancer and is associated with a favorable toxicity profile. In a population with recent exposure to platinum, a PFI of less than 3 months was the major factor influencing response to chemotherapy. © 2007 Elsevier Inc. All rights reserved.
Keywords: Chemotherapy; Cisplatin; Gemcitabine; Ovarian cancer; refractory; Resistant